From Growth Theory to Technology Policy - Coordination Problems in Theory and Practice - Tor Jakob Klette; Jarle Møen (University of Oslo, Department of Economics, 1998)
Economists, in particular Bresnahan and Trajtenberg (1995), have recently drawn attention to the importance of generic or general purpose technologies (GPTs) and their significance for economic growth. An interesting part of this research identies coordination problems in the introduction of GPTs, and the potentially large benefits in coordinating research and product development. Thinking about information technology as a GPT, with the associated coordination problems, seems to fit well with the motivation behind governmental support schemes to IT and related high-tech industries in Norway. The first part of our study focuses on a series of such IT-programs that have been implemented in Norway from the early 1980s with the objective of coordinating the development of information technology and its application throughout the economy. We examine in some detail the largest of these IT-programs through its planning and implementation stages and emphasize how closely it is connected to recent economic analysis of GPTs. The second part of our study examines to what extent these governmental plans and subsidy schemes have been successful in creating economic results in terms of growth and profits in the IT and IT-related industries. In the final part of the paper we discuss some of the lessons about the problems with technology policy at a practical level.
Keywords: 330